Teams and working conditions in mobile pre-hospital care services: an integrative review - Daiane Dal Pai; Maria Alice Dias da Silva Lima; Kelly Piacheski Abreu; Paula Buchs Zucatti; Liana Lautert (Universidade Federal de Goias, 2015)
Study to identify, analyze and summarize the findings available in the literature on the composition of teams and working conditions in Mobile  Pre-Hospital Care Services  (PHC).  Integrative review to search the Base  de Dados  de  Enfermagem [Nursing Database] (BDEnf), the Cumulative  Index  to  Nursing  and  Allied  Health  Literature (CINAHL),  the Latin American and Caribbean Health Sciences Literature (LILACS), PubMed,  SCOPUS,  Web  of  Science and the portal of journals from the Scientific  Electronic  Library Online  (SciELO). Eighteen articles met the inclusion criteria and were selected. The composition of the teams for PHC services is diversified on the international stage, with the increase in responsibilities assumed by paramedics and the benefits of the specialized nurse's and doctor's presence in the teams being portrayed, which are scarce in some countries.  Working conditions reveal risky places of work, intense psychological demands, work overload, dissatisfaction and inadequate resources in most services.